Effect of perioperative dexmedetomidine on the endocrine modulators of stress response: a meta-analysis - Wang, Xian-wang; Cao, Jiang-bei; Lv, Bao-sheng; Mi, Wei-dong; Wang, Zhuo-qiang; Zhang, Changsheng; Wang, Heng-lin; Xu, Zhen (Clinical and experimental pharmacology & physiology, 2015)
Summary This study examined the effects of perioperative dexmedetomidine treatment on physiological modulators of surgical stress response. The quality of the included studies was assessed prior to performing meta‐analyses of the weighted mean differences in the changes from baseline of stress hormones and interpreted in the light of statistical heterogeneity between the studies. Nineteen studies (844 surgical subjects) data were used for this meta‐analysis. Dexmedetomidine administration significantly decreased blood cortisol levels (μg/dL) postoperatively (mean difference with 95% confidence interval (CI) from controls: −18.78 (−28.45, −9.10); P < 0.05). In the subgroup analysis, the mean difference between dexmedetomidine‐treated and saline‐treated subjects in the changes from baseline of the cortisol levels was −20.10 (−30.96, −9.25; P < 0.05) but, between dexmedetomidine‐ and comparator‐treated subjects, it was not statistically significantly different (−15.13 (−49.78, 19.52); P < 0.05). Compared with controls, dexmedetomidine treatment also decreased adrenaline and noradrenaline levels significantly (mean difference in the percent changes from baseline: −90.41 (−145.79, −35.03)%; P < 0.05 and −62.82 (−85.47, −0.40.17)%; P < 0.05, respectively). Dexmedetomidine also decreased prolactin levels with a mean difference of −19.42 (−39.37, 0.52) μg/L (P = 0.06). In conclusion, perioperative use of dexmedetomidine reduces serum catecholamine and cortisol levels but the decrease in cortisol levels was not statistically different from the comparator anaesthetics. More data will be required to assess the effects of dexmedetomidine on corticotropin, prolactin, and growth hormone.